THE REPRESENTATION OF UZBEK PEOPLE’S TRADITIONAL LIFE AND CULTURAL HERITAGE IN HOUSE MUSEUMS (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the representation of the traditional lifestyle and cultural heritage of the Uzbek people in house museums, using the house museums of Khamza Khakimzoda Niyoziy and Fayzulla Khujayev as examples. The study highlights the role of museum expositions in reconstructing historical periods and their importance in reflecting everyday life, architecture, social relations, and cultural values. It also examines the socio-cultural life of Uzbek society in the late 19th and early 20th centuries through museum exhibits. House museums are assessed not only as institutions preserving historical memory but also as significant scientific and cultural sources that promote national heritage.